Proceedings of the 2015 International Conference on Applied Science and Engineering Innovation 2015
DOI: 10.2991/asei-15.2015.380
|View full text |Cite
|
Sign up to set email alerts
|

Effects of postcure temperature on mechanical properties of resin mineral composite for precision machine tool

Abstract: Resin mineral composite has drawn much attention in the field of elementary machine components due to its excellent damping property. The effects of postcure temperature on mechanical properties of resin mineral composite were investigated in this paper. Research results showed that the glass-transition temperature of resin matrix, the surface hardness of resin matrix, the compressive strength of resin matrix, and the compressive strength of resin mineral composite increased with the increasing postcure temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A variety of postcure temperatures can effectively change the T g of matrix and mechanical properties of RMC. 21 Wei et al 22 found that addition of carbon nanotubes to a polymer matrix would increase the glass transition temperature (T g ) and thermal expansion and duffusion coefficients in the composite above T g . Wong and Bollampally 23 studied the CTE of polymer composite filled with ceramic particles for electronic packaging.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of postcure temperatures can effectively change the T g of matrix and mechanical properties of RMC. 21 Wei et al 22 found that addition of carbon nanotubes to a polymer matrix would increase the glass transition temperature (T g ) and thermal expansion and duffusion coefficients in the composite above T g . Wong and Bollampally 23 studied the CTE of polymer composite filled with ceramic particles for electronic packaging.…”
Section: Introductionmentioning
confidence: 99%